2019
DOI: 10.1002/pmic.201900160
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p38 MAPK in Triacylglycerol Accumulation during Apoptosis

Abstract: Lipids are emerging as key regulators of apoptosis. Specific lipid species are associated with apoptosis with important functional roles, but the understanding of the regulation of these lipid species is still limited. It has been previously shown by our laboratory that polyunsaturated triacylglycerols accumulate and get stored within lipid droplets during apoptosis via activated glycerolipid biosynthesis. In this work, the biochemical mechanisms that result in the activation of glycerolipid biosynthesis and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…At present, it has been confirmed that NF-κB and MAPK, which widely exist in various cells of the body, are closely related to inflammation, liver fibrosis and liver failure in the development of NAFLD and NASH, and play an important role (24). Additionally, MAPK has been shown to regulate triacylglycerol biosynthesis through diacylglycerol acyltransferase during apoptosis and to be involved in the accumulation of cellular lipid droplets and polyunsaturated fatty acids (25). Furthermore, Kong et al discovered that ICA inhibited tumor necrosis factor-α (TNF-α)/interferon (IFN)-γ-induced inflammatory responses via inhibiting the substance P and p38-MAPK signaling pathways in human keratinocytes (26).…”
Section: Discussionmentioning
confidence: 99%
“…At present, it has been confirmed that NF-κB and MAPK, which widely exist in various cells of the body, are closely related to inflammation, liver fibrosis and liver failure in the development of NAFLD and NASH, and play an important role (24). Additionally, MAPK has been shown to regulate triacylglycerol biosynthesis through diacylglycerol acyltransferase during apoptosis and to be involved in the accumulation of cellular lipid droplets and polyunsaturated fatty acids (25). Furthermore, Kong et al discovered that ICA inhibited tumor necrosis factor-α (TNF-α)/interferon (IFN)-γ-induced inflammatory responses via inhibiting the substance P and p38-MAPK signaling pathways in human keratinocytes (26).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study has demonstrated that MAPK regulated triacylglycerol biosynthesis through diacylglycerol acyltransferase during apoptosis; also, MAPK was involved in lipid droplet and polyunsaturated fatty acid accumulation in this process. [ 29 ] In addition, Kong et al discovered that ICA inhibited TNF‐α/IFN‐γ‐induced inflammatory responses via inhibiting substance P and p38‐MAPK signaling pathways in human keratinocytes. [ 30 ] In our research, ICA could regulate lipid droplet formation and inflammatory response in cells through regulating NF‐κB and MAPK signaling, consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…That, beta-arrestin-1-dependent signaling pathway for p38 mitogen-activated protein kinase activation by beta2-adrenergic receptors [27]. That the rich Proline in activate hydrophobic acids synthesis (regulated by pyrimidine TAT TAC kinases) which activate IFN-beta and GC-beta ( mediated by MAPK function and by synthase for Acyl-COA-beta synthesis) that activate B-arrestins synthesis which adopt the glycoprotein ratio through binding to GPCR-B for stimulating ACE for Ang2-AT2 synthesis (from Ang1-AT1) which protect and adopt heart layers function , and also promote VEGF-A synthesis for adopting microvascular functions.…”
Section: Endocardial Layer Include Fibrinolysis Adopted By B-arrestin...mentioning
confidence: 99%